Do we live on the End of the World? - Benjamin Muntz; Antonio Padilla; Paul M. Saffin (Journal of High Energy Physics)
Abstract We propose a scenario of a de Sitter universe living on an End-of-the-World brane. Motivated by the Swampland programme and in particular the Cobordism Conjecture, we consider a compact region of AdS5 nucleating from nothing, with a dS4 living on its boundary. We show that it can equivalently be interpreted as an up-tunnelling from AdS5 with cosmological constant Λ → −∞, following Brown and Dahlen’s proposal for ‘nothing’. Their picture naïvely leads to the conclusion that the brane has infinite negative tension. But we show that it becomes finite and positive once we employ holographic renormalization, recovering the Bubble of Something where the domain wall becomes a boundary of spacetime. The same holds true in any number of dimensions and, moreover, at the level of metric perturbations. This provides motivation for alternative routes of obtaining cosmology from quantum gravity or string theory using domain walls, departing from conventional vacuum approaches.